THE ANXIETY THAT CONVEYING TRAGEDY IN OTHELLO DRAMA BY SHAKESPEARE - Maharani, Puja; Arianto, Tomi (Universitas Putera Batam, 2022)
Humans are always in touch with the needs in this life. In order to survive, one of the most important examples is the need for safety needs. The phenomenal drama Othello by Shakespeare was chosen as the main data source in this research. This research aimed to analyze the unfulfilled of safety needs in the form of anxiety and its impact on the main character in Shakespeare's drama